Association between relative handgrip strength and prediabetes among South Korean adults - Jang, Bich Na (PLoS One, 2020)
BACKGROUND: Diabetes is a progressive disease, and thus, it is important to prevent diabetes at the prediabetes stage. Although the loss of muscle strength and prediabetes are associated, few studies have examined relative handgrip strength (RHGS), which can be an indicator of both muscle strength and adiposity. Therefore, our study aimed to examine the association between RHGS and prediabetes (HbA1c level >5.7%) stratified by sex due to sex differences in strength. METHODS: We analyzed data from the 2016–2018 Korean National Health and Nutrition Examination Survey. Prediabetes was defined using the HbA1c cut-off level of 5.7–6.4%, identified by the American Diabetes Association. RHGS was calculated as the maximal absolute handgrip strength of both hands divided by body mass index and was divided into sex-specific quartiles. Multiple logistic regression analysis was performed to determine the association between sex-specific RHGS and prediabetes. RESULTS: Among the total participants, 13,384 did not have diabetes. In men, the low and mid-low RHGS groups had increased odds of prediabetes (low group, odds ratio [OR]: 1.42, 95% confidence interval [CI]: 1.10–1.82; mid-low group, OR: 1.32, 95% CI: 1.04–1.67). However, no significant differences were observed between the corresponding female groups. Moreover, central obesity and lower RHGS were strongly associated with prediabetes in men (low group, OR: 2.40, 95% CI: 1.52–3.80; mid-low group, OR: 2.00, 95% CI: 1.26–3.17; mid-high group, OR: 1.76, 95% CI: 1.11–2.81), and a trend was observed (p = 0.0026). CONCLUSION: RHGS could be a practical and inexpensive tool for predicting diabetes in men. Programs aimed at preventing diabetes need to include exercise routines for improving muscle strength, and further research through longitudinal studies is required to investigate the causality of RHGS on the risk of prediabetes.